Selective photodepletion of malignant T cells in extracorporeal photopheresis with selenorhodamine photosensitizers. Issue 17 (1st September 2016) - McIver, Zachariah A.; Kryman, Mark W.; Choi, Young; Coe, Benjamin N.; Schamerhorn, Gregory A.; Linder, Michelle K.; Davies, Kellie S.; Hill, Jacqueline E.; Sawada, Geri A.; Grayson, Jason M.; Detty, Michael R.
Graphical abstract: Abstract: Extracorporeal photopheresis (ECP) has been used successfully in the treatment of erythrodermic cutaneous T cell lymphoma (CTCL), and other T cell-mediated disorders. Not all patients obtain a significant or durable response from ECP. The design of a selective photosensitizer that spares desirable lymphocytes while targeting malignant T cells may promote cytotoxic T cell responses and improve outcomes after ECP. A series of selenorhodamines built with variations of the Texas red core targeted the mitochondria of malignant T cells, were phototoxic to malignant T cells presumably via their ability to generate singlet oxygen, and were transported by P-glycoprotein (P-gp). To determine the selectivity of the photosensitizers in the ECP milieu, staphylococcal enterotoxin B (SEB)-stimulated and non-stimulated human lymphocytes were combined with HUT-78 cells (a CTCL) to simulate ECP. The amide-containing analogues of the selenorhodamines were transported more rapidly than the thioamide analogues in monolayers of MDCKII-MDR1 cells and, consequently, were extruded more rapidly from P-gp-expressing T cells than the corresponding thioamide analogues. Selenorhodamine6 with the Texas red core and a piperidylamide functionality was phototoxic to >90% of malignant T cells while sparing >60% of both stimulated and non-stimulated T cells. In the resting T cells, (63 ± 7)% of the CD4+ T cell compartment, and (78 ± 2.5)% of the CD8+ cytotoxic T cell population were preserved, resulting in an enrichment of healthy and cytotoxic T cells after photodepletion.